Social Panorama of Latin America 2000–2001 - Nations Unies (United Nations, 2002)
The social situation in Latin America in the late 1990s was influenced by the slowdown and greater volatility of economic growth. Despite the economic recovery seen in 2000, the effects of the contraction were felt in many countries of the region. This publication devotes special attention to poverty trends and rates in the late 1990s, inequality in income distribution, the employment and unemployment situation, the countries' progress in raising social expenditure and the distributive effects of such increases. In it's final chapter, this publication reviews the Governments' agenda in relation to family issues. The analyses of each of the topics covered in the five chapters that make up the Social Panorama combine an examination of the latest trends in the main social indicators with an assessment of the trends seen throughout the 1990s.